Study on the Deformation Mechanism of Soft Rock Roadway under Blasting Disturbance in Baoguo Iron Mine - Hong-di Jing; Yuan-hui Li; Kun-meng Li (Shock and Vibration)
In order to study the deformation mechanism of soft rock roadway in underground mines, it is necessary not only to study the influence of the dynamic disturbance caused by the cyclic mining blasting vibration on the stability of the soft rock roadway but also to study the degradation of the roadway surrounding rock itself and other factors. The paper presented a synthetic research system to investigate the factors that influence roadway rock structure deterioration in Baoguo Iron Mine. Firstly, the stability of rock mass was analyzed from the perspective of the physical and structural characteristics of the rock mass. Afterwards, according to monitoring data of mining blasting vibration, a suitable safety blasting prediction model for Baoguo Iron Mine was determined. And then, combining the results of mining blasting vibration monitoring and deformation monitoring, the effect of cyclic mining blasting on the stability of the soft rock roadway was obtained. By systematically studying the intrinsic factors of rock quality degradation and external environmental disturbances and their interactions, this paper comprehensively explores the deformation mechanism of soft rock roadway and provides the support for fundamentally solving the large deformation problems of soft rock roadway in underground mines.